2016
DOI: 10.2147/ppa.s103840
|View full text |Cite
|
Sign up to set email alerts
|

Using the Dynamic Appraisal of Situational Aggression with mental health inpatients: a feasibility study

Abstract: PurposeThis paper aims to explore the acceptability of Dynamic Appraisal of Situational Aggression (DASA) from the perspective of patients, its actual use by mental health nurses, and the predictive validity of the DASA instrument.MethodsA feasibility study design incorporating quantitative and qualitative components was used. The study was conducted in three mental health inpatient units at three hospitals in southern Finland. Quantitative data were used to explore demand (nurses’ actual use of the DASA), lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The projection formular was adopted from similar studies. 2,28 There are 246 wards in Lagos State and 24 wards were randomly selected by balloting, and these served as sampling units for this study. One hundred and thirteen enumeration areas (EAs) (representing 30%) of the total EAs were selected randomly.…”
Section: Methodsmentioning
confidence: 99%
“…The projection formular was adopted from similar studies. 2,28 There are 246 wards in Lagos State and 24 wards were randomly selected by balloting, and these served as sampling units for this study. One hundred and thirteen enumeration areas (EAs) (representing 30%) of the total EAs were selected randomly.…”
Section: Methodsmentioning
confidence: 99%
“…Fifty-two studies were synthesised in this review which spanned nine national contexts. Nine studies were conducted in the United Kingdom (UK) [ 30 – 38 ] and Australia [ 39 – 47 ], eight in the United States (US) [ 48 – 55 ], three in Canada [ 56 58 ], two in Finland [ 59 , 60 ] and one each in New Zealand [ 61 ], Denmark [ 62 ], Belgium [ 63 ] and the Netherlands [ 64 ]. By contrast the grey literature spanned only two national contexts, the UK and US.…”
Section: Resultsmentioning
confidence: 99%
“…All 52 studies were classified using the MMAT as follows: two Quantitative Randomised [ 31 , 48 ] eight Quantitative Non-randomised [ 36 , 42 , 45 , 48 , 50 , 55 , 64 , 74 , 79 ], fourteen Quantitative Descriptive [ 37 , 43 , 49 , 51 54 , 57 , 61 , 62 , 70 , 72 , 73 , 76 ], nine Qualitative [ 33 35 , 39 , 41 , 56 , 58 , 59 , 66 ], and five Mixed Methods [ 30 , 44 , 60 , 63 , 71 ]. Fourteen studies (all grey literature) could not be classified using MMAT as they used a selection of quality improvement designs including four which used PDSA cycles [ 38 , 40 , 65 , 69 ], seven used other QI methods [ 32 , 46 , 47 , 67 , 68 , 77 , 81 ] and in three studies the methodology was unclear [ 76 , 78 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The tool has been further validated in another four studies by Lantta et al (2016), Chu et al (2013), Griffith et al (2013), and Vojt et al (2010) with moderate to strong predictive validity. These studies further reported that the predictive validity of the DASA was not significantly different from that of the BVC (Chu et al 2013;Ogloff & Daffern 2006) and that the tool took less than 5 min to complete (Chu et al 2013;Griffith et al 2013;Lantta et al 2016;Ogloff & Daffern 2006). Vojt et al (2010), however, reported that the predictive power of the DASA was consistent for incidents of verbal aggression only, and not for physical aggression or all other aggressive incidents.…”
Section: Dynamic Appraisal Of Situational Aggression (Dasa)mentioning
confidence: 99%